Mathematical Taught Facilities at Civil-Engineering Faculties - I. A. Holubeva (Наука и техника)
An orientation of mathematical teaching process of civil-engineering students to higher quality of their training has required not only to reconsider the traditional mathematical taught facilities but also add new components that are considered in this paper.